Rapid Recovery from Acute Liver Failure Secondary to Pancreatoduodenectomy-Related Non-Alcoholic Steatohepatitis - Kazushige Nirei; Norikazu Ogihara; Wataru Kawamura; Woodea Kang; Mitsuhiko Moriyama (Case Reports in Gastroenterology, 2013)
This report describes a case of liver failure secondary to pancreatoduodenectomy and rapid recovery following treatment. A 68-year-old woman with cancer on the ampulla of Vater underwent surgery for pancreatoduodenectomy. The patient developed liver failure 3 months postsurgically. She was hospitalized after presenting with jaundice, hypoalbuminemia and decreased serum zinc. Computed tomography (CT) of the abdomen showed a reduction in CT attenuation values postoperatively. We suspected fatty liver due to impaired absorption caused by pancreatoduodenectomy. We initiated treatment with branched-chain amino acids and a zinc formulation orally. Trace elements were administered intravenously. Two months after treatment, there was a noticeable improvement in CT findings. The patient’s jaundice and hypoalbuminemia prompted a liver biopsy, which led to a diagnosis of non-alcoholic steatohepatitis.